The theses for MD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2011)
Yu.V. Korotchayeva – Clinical value of IL-6 assessment in blood serum and urine and cytochrome Р450 in liver tissue at chronic hepatitis C patients.L.R. Idrisova – Value of a latent HBV-infection in progression of chronic liver diseases.T.A. Batyukhno - Chronic pancreatitis: disorders of protective immune mechanisms and their pharmacological treatment.S.P. Fedorov – Pharmakokinetics and pharmacodynamics of rabeprazole.